Winning in China : 8 stories of success and failure in the world's largest economy - Sang, Lele (Wharton School Press, 2021)
If Amazon can't win in China, can anyone? When Amazon CEO Jeff Bezos visited China in 2007, he expected that one day soon China would be a double-digit percentage of Amazon's sales. Yet, by 2019, Amazon, the most powerful and successful ecommerce company in the world, had quit China. In Winning in China: 8 Stories of Success and Failure in the World's Largest Economy, Wharton experts Lele Sang and Karl Ulrich explore the success and failure of several well-known companies, including Hyundai, LinkedIn, Sequoia Capital, and InMobi, as more and more businesses look to reap profits from the demand of 1.4 billion people. Sang, Global Fellow at the Wharton School of the University of Pennsylvania, and Ulrich, Vice Dean of Entrepreneurship and Innovation at the Wharton School, answer four critical questions: Which factors explain the success (or failure) of foreign companies entering China? What challenges and pitfalls can a company entering China expect to encounter? How can a prospective entrant realistically assess its chances? Which managerial decisions are critical, and which approaches are most effective? Sang and Ulrich answer these questions by examining the stories of eight well-known and respected companies that have entered China. They study: How Norwegian Cruise Line's entry into China displays how cultural differences can boost or sink different companies; How Intel, one of the oldest, most respected firms in Silicon Valley, thrived in a country that seems to favor agile upstarts; How Zegna, the Italian luxury brand, has emerged as another surprising success story and how it plans to navigate new headwinds from the COVID-19 pandemic. Through these engaging and illuminating stories, Sang and Ulrich offer a framework and path for organizations looking for a way to successfully enter the world's largest economy. History can be a teacher, and China, a country with 3,500 years of written history, has much to teach.--Provided by publisher.